Abrupt watercourse formation in a semiarid sedimentary landscape of central Argentina: The roles of forest clearing, rainfall variability and seismic activity - Contreras, S. (2012)
In a semiarid sedimentary catchment of central Argentina, we describe a recent process of landscape dissection, abrupt canyon and watercourse formation and soil salinization. We link these adverse hydrological and geomorphological transformations to three potentially important drivers: precipitation increase, seismic activity and deforestation. Remote sensing imagery in the last 48years showed an exponential increase in the length of streams, with drainage density values tripling to reach 0.22km km2. During the same period, forest area declined from 47% to 10%, at the expense of agriculture expansion. A 3.4-fold expansion of surface water bodies and water table level raise of 0.15m y-1 over the last 35years was observed. Discharge of a new stream at the middle of the basin ranged between 0.25 and 0.45m3 s-1 accompanied by a large and stable load of salts (~0.7g l-1). Nil recharge and large vadose accumulation of salts in dry forests stands contrasted with recharge rates of ~16mm y-1 and salt-leached profiles under agriculture. Although the process of landscape dissection occurred during decades of higher than average precipitation, extreme rainfall events and seismic activity were not exceptional in that period. Results suggest that the replacement of forests by annual crops played a more important role, reducing evapotranspiration, triggering the onset of groundwater recharge and favouring subsurface through piping/sapping processes. The abrupt landscape dissection shows no signs of stabilization at the present and may only be ameliorated through changes in vegetation that restore the original non-flow condition of the forest.